The little black book of innovation : - Anthony, Scott D. (Harvard Business Review Press, 2017)
In The Little Black Book of Innovation, long-time innovation expert Scott D. Anthony draws on stories from his research and field work with companies like Procter & Gamble to demystify innovation. Anthony presents a simple definition of innovation and illuminates its vital role in organizational success and personal growth. Anthony also provides a powerful 28-day program for mastering innovations key steps: finding insight, generating ideas, building businesses, and strengthening capabilities.